The effect of corporate entrepreneurship, innovation and strategic renewal on business performance - Ruben Guevara, Felipe Jánica,; Hernández-Fernández, Lissette (Opción)
This article provides a conceptual framework trying to explain the effect of Corporate Entrepreneurship that encompasses Innovation and Strategic Renewal on Business Performance (Business Failure or Organizational Decline) in Colombian companies. This research uses the information provided by the Superintendency of Corporations of Colombia of companies that have entered the restructuring process during the last ten years. Primary and secondary data were collected from the 131 companies. The results show that innovation affects corporate entrepreneurship, and there is a direct impact on business performance, but there is no effect on organizational decline.